PTU-158 The Influence of Social Class on Progression of Barrett's Oesophagus to Oesophageal Adenocarcinoma. (17th August 2016) - Bhattacharjee, S; Caygill, CPJ; Gatenby, PAC; Watson, A
Abstract : Introduction: The incidence of oesophageal adenocarcinoma (OAC) has been rapidly increasing over the last three to four decades in many western nations, including the UK. Barrett's oesophagus (BO) is the only known precursor condition for OAC. Surveillance of BO may be undertaken with the goal of detecting dysplasia and early neoplasia prior to the development of incurable cancer. The identification of subpopulations of subjects at highest risk of cancer development should allow more effective targeted surveillance. Methods: Clinical records of 2896 patients from two centres in the UK, who have consented and registered with the UK Barrett's Oesophagus Registry (UKBOR), were used for the purpose of this study. Data on patient's occupation were obtained from hospital records, or from death certificates where available. The most widely used measure of social class in the UK is the 'Registrar General's Classification' which assigns a social class category (I-V with subdivision of class III into III N [non-manual workers] and III M [manual workers] against individual occupation. Social class I are the professionals and higher managers, II and III are junior managers/supervisors, III and IV comprises of semiskilled and manual occupations and those in V are unskilled workers. A Chi-squared goodness of fit test was used to test for significance of the association of social class in both BO and OAC. Results: In the BO group, 1824 people had usable information on occupation. Table 1 shows the observed (O) cases of BO and OAC in each of the social classes and the number of expected (E) cases of OAC assuming an equal proportion of social class developed OAC (p-value – 0.003) The O/E results demonstrate an excess of patients progressing to OAC in social class III M, and a lower than expected number of cases in social classes I, III N and V. Conclusion: Our study shows that more OAC is observed in BO patients in social class III M than expected whereas fewer are observed in social class I, IIIN and V than expected. References: 1 Jansson C, Johansson AL, Nyren O, et al . Socioeconomicfactors and risk of esophageal adenocarcinoma: a nationwide Swedish case-control study. Cancer Epidemiol Biomarkers Prev 2005;14 : 1754–1761. 2 Islami F, Kamnagar F, Nasrollahzadeh D, et al . Socio-economic status and oesophageal cancer: results from a population based case-control study in a high risk area. Int J Epidemiol 2009;38 :978–988. Disclosure of Interest: None Declared